pengaruh lingkungan kerja dan beban kerja terhadap kinerja karyawan pada Perusahaan Kelapa Sawit - ali, aji saidina; Septayudha, Irwan (Jurnal Ilmu Manajemen, 2022)
This study aims to identify and analyze To find out and analyze the effect of the work environment and workload on employee performance at the oil palm company in ogan komering ilir, this research was conducted in one of the ogan komering ilir palm oil mill companies. The population and sample in this study were all employees of the palm oil mill company Ogan Komering Ilir. The data used were primary data obtained from the results of distributing questionnaires through HRD Distributed with Googlefrom. The method used is Likert Scale. The data analysis technique used is descriptive qualitative. The test shows that the first hypothesis is T test (Partial Significance Test) Work environment on employee performance has no effect, work environment variable has no effect on employee performance (Y) this is evidenced by a sig value of 0.62 > 0.05. Testing the second hypothesis shows that the T Test (Partial Test) of Workload on Employee Performance has an effect on the variable Workload has a significant influence on Employee Performance (Y) this is evidenced by the sig value of 0.000 <0.05. Testing the third hypothesis F test (simultaneous test) shows that it affects the employee performance variable (Y) this is evidenced by the sig value of 0.000 <0.05